2002
DOI: 10.1023/a:1021021625569
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Lafutidine is a new type of antiulcer drug, possessing both an antisecretory effect, exerted via a blockade of the histamine H2 receptor, and gastroprotective activity, mediated by capsaicin-sensitive afferent nerves (CSN). In the present study, we examined the effect of lafutidine on gastric mucosal blood flow (GMBF) and duodenal HCO3- secretion (DAS) under basal and acid-stimulated conditions in rats. Under urethane anesthesia, GMBF was measured using a laser Doppler flowmeter in a chambered stomach before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The precise mechanism by which Laf exerts its effects is unknown; nevertheless, denervation of CSAN abrogates the protective effects of Laf, suggesting involvement of the capsaicin pathway. In vitro studies have failed to document a direct interaction between Laf and TRPV1 [12, 14], whereas Laf potentiates Cap-induced CGRP release from the gastric mucosa [14], suggesting that Laf sensitizes TRPV1 or interacts at alternate components of the capsaicin pathway. Our results demonstrated that luminal Laf perfusion increased blood flow in the absence of perfused luminal acid and that Laf enhanced acid-induced hyperemia, both mediated by CSAN, supporting our hypothesis that Laf sensitizes TRPV1 or submucosal afferent nerves.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism by which Laf exerts its effects is unknown; nevertheless, denervation of CSAN abrogates the protective effects of Laf, suggesting involvement of the capsaicin pathway. In vitro studies have failed to document a direct interaction between Laf and TRPV1 [12, 14], whereas Laf potentiates Cap-induced CGRP release from the gastric mucosa [14], suggesting that Laf sensitizes TRPV1 or interacts at alternate components of the capsaicin pathway. Our results demonstrated that luminal Laf perfusion increased blood flow in the absence of perfused luminal acid and that Laf enhanced acid-induced hyperemia, both mediated by CSAN, supporting our hypothesis that Laf sensitizes TRPV1 or submucosal afferent nerves.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being a potent H2 receptors antagonist [12], lafutidine also activates capsaicin-sensitive afferent neurons and stimulates the release of calcitonin gene-related peptide (CGRP), which inhibits acid secretion and stimulates mucosal blood flow [13–15]. The gastro protective action of lafutidine includes increase in mucin biosynthesis via stimulation of nitric oxide production [11, 16], increasing the thickness of the surface mucus gel layer [17], and maintaining gastric mucosal blood flow and bicarbonate response [18]. Lafutidine has been elaborately studied internationally in various indications like gastritis, and gastric and peptic ulcer, while recent focus has also shifted to its use in gastroesophageal reflux disorder (GERD) [19–23].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from this mechanism of action it is also conceivable that lafutidine facilitated gastric acid elimination by dilution with fluid and acid-neutralizing factors. The capacity of lafutidine to stimulate secretory processes other than acid secretion in the upper gut is supported by its effect to increase acid-stimulated duodenal bicarbonate secretion [7]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is evidence that the gastroprotective action of lafutidine involves release of neuropeptides from afferent nerve endings in the stomach [7,8]. In view of this pharmacological profile the question arose as to whether lafutidine would be able to modify vagal afferent signalling of gastric acid challenge to the brainstem.…”
Section: Introductionmentioning
confidence: 99%